Impeding access: The frequency and characteristics of improper scooter, bike, and car parking. (March 2020) - Brown, Anne; Klein, Nicholas J.; Thigpen, Calvin; Williams, Nicholas
Abstract: Many cities are grappling with how to regulate new shared mobility modes, including dockless e-scooters and bikes (i.e., "micromobility"). Transportation planners in these cities are particularly concerned about micromobility parking regulations, which have implications for the safety and mobility of riders and the general public. In this research, we investigate the parking practices as well as the frequency and types of parking violations of three types of vehicles operating on city sidewalks and streets: e-scooters, bikes, and motor vehicles. We collected original data on 3666 e-scooters, bikes, motor vehicles, and sidewalk objects in Austin, TX, Portland, OR, San Francisco, CA, Santa Monica, CA, and Washington, DC, to examine micromobility and motor vehicle parking practices. We find that motor vehicles impede access far more (24.7%) than bikes (0.3%) and e-scooters (1.7%). Ride-hail and food delivery drivers disproportionately impede access. Motor vehicles often impeded other travelers' access when dropping off or picking up people or food while double parking, parking in "No Parking" areas, or blocking driveways. Our findings suggest that micromobility companies are just one of several technology-enabled transportation services that should motivate cities to rethink parking policies. Highlights: Observation of over 3600 bikes, scooters, and cars shows parking behaviors in five American cities. Seven of 865 (0.8%) bicycles and scooters were improperly parked. Nearly one-quarter (24.7%) of motor vehicles were improperly parked. Ride-hail, taxi, delivery, and commercial vehicles accounted for 64% of motor vehicle violations.